Development of a Systems Science Curriculum to Engage Rural African American Teens in Understanding and Addressing Childhood Obesity Prevention. (June 2018) - Frerichs, Leah; Hassmiller Lich, Kristen; Young, Tiffany L.; Dave, Gaurav; Stith, Doris; Corbie-Smith, Giselle
Engaging youth from racial and ethnic minority communities as leaders for change is a potential strategy to mobilize support for addressing childhood obesity, but there are limited curricula designed to help youth understand the complex influences on obesity. Our aim was to develop and pilot test a systems science curriculum to elicit rural African American youth perspectives on childhood obesity and enhance their understanding of and support for obesity prevention solutions. The curriculum was designed so it could be integrated with existing positive youth development curricula that help youth advocate for and implement identified solutions. We conducted four workshop sessions with youth that engaged them in systems learning activities such as guided systems diagramming activities. The participants ( n = 21) completed validated surveys presession and postsession that assessed their causal attributions of obesity and support for obesity prevention policies. The youths' perception that environmental factors cause obesity increased ( p < .05), and perceptions that individual behavior and biology cause obesity did not change. Their support for policies that addressed food access and food pricing significantly increased ( p < .05). The youths' system diagrams elucidated links between multilevel factors such as personal attitudes, social influence, and the built environment, which provides important information for designing synergistic solutions. The changes we observed in youths' perceptions of obesity and support for policy changes have important implications for youths' interest and willingness to advocate for social and environmental changes in their community. The strategies have a promising role in supporting community mobilization to address childhood obesity.